Republic of Belarus : Corruption Vulnerability Scan - World Bank (Washington, DC, 2013)
The Corruption Vulnerability Scan (CVS) is an internal Bank document aimed at providing a better understanding on the Bank's vulnerability in extending assistance to Belarus, and making suggestions as to how to reduce risks in the use of Bank funds, while improving results on the ground. The CVS team visited Belarus in March 2007. Its main conclusion is that the vulnerability to corruption of Bank funds and activities funded from loan proceeds in Belarus is low, as long as Bank fiduciary procedures are used and implementation is closely supervised. The report is in three parts: Corruption and Anti-Corruption in Belarus, Public Finance Management and the Bank Portfolio.